Purification, characterization and radioimmunoassay of adenosine deaminase from human leukaemic granulocytes. - Wiginton, D A (1981)
Adenosine deaminase was purified 3038-fold to apparent homogeneity from human leukaemic granulocytes by adenosine affinity chromatography. The purified enzyme has a specific activity of 486 mumol/min per mg of protein at 35 degrees C. It exhibits a single band when subjected to sodium dodecyl sulphate/polyacrylamide-gel electrophoresis, non-denaturing polyacrylamide-gel electrophoresis and isoelectric focusing. The pI is 4.4. The enzyme is a monomeric protein of molecular weight 44000. Both electrophoretic behaviour and molecular weight differ from those of the low-molecular-weight adenosine deaminase purified from human erythrocytes. Its amino acid composition is reported. Tests with periodic acid-Schiff reagent for associated carbohydrate are negative. Of the large group of physiological compounds tested as potential effectors, none has a significant effect. The enzyme is specific for adenosine and deoxyadenosine, with Km values of 48 microM and 34 microM respectively. There are no significant differences in enzyme function on the two substrates. erythro-9-(2-Hydroxy non-3-yl) adenine is a competitive inhibitor, with Ki 15 nM. Deoxycoformycin inhibits deamination of both adenosine and deoxyadenosine, with an apparent Ki of 60-90 pM. A specific antibody was developed against the purified enzyme, and a sensitive radioimmunoassay for adenosine deaminase protein is described.